Ответ:
Объяснение
1) {x-2y=5 |*(-3)
{3x+5y=26
---------------
{-3x+6y=-15
{3x+5y=26 ( складываем уравнения )
11y=11
y=1
--------------------------------------
2) {3x-y=1 |*8
{3x+8y=19
{24x-8y=8
{3x+8y=19 ( складываем уравнения )
27x=27
x=1
Думаю, принцип понятен. Последнее так же
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение
1) {x-2y=5 |*(-3)
{3x+5y=26
---------------
{-3x+6y=-15
{3x+5y=26 ( складываем уравнения )
11y=11
y=1
--------------------------------------
2) {3x-y=1 |*8
{3x+8y=19
---------------
{24x-8y=8
{3x+8y=19 ( складываем уравнения )
27x=27
x=1
Думаю, принцип понятен. Последнее так же